A Study of Smart Power Control Algorithm Using RF Communication in Smart Home Environment. (16th December 2013) - Shin, Su-hong; Do, Kyoung-hwa; Koh, Byoung-soo
Abstract : Today's technologies in the IT area face the era of combination and convergence of technologies in many different areas. Through the natural interaction between people and devices in the environment where various kinds of devices are connected over a single network, they have been developing from human-oriented service technologies to smart and futuristic home technologies. Smart home technology is one of them. It is a technology of establishing a digital home in which various kinds of home appliances are connected over a home network and diverse services are provided for users regardless of time and place. Technologies in the IT area are combined with technologies in many different areas, creating and producing numerous technologies. Also, much research on smart home, the theme of this work, has actively been conducted. In this work, the use of a current booster, an AC/DC converter, and a DC/DC converter to operate electric lights; this work implements the smart power control system using standby power and RF communication, among smart home technologies.